If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2+5x)/15+(3x-1)/2=(3x-3)/5-(1-3x)/2
We move all terms to the left:
(2+5x)/15+(3x-1)/2-((3x-3)/5-(1-3x)/2)=0
We can not solve this equation
| v-6,43=1,77 | | x-52x-9=4x+19 | | 7a+8=14a | | 7n-1=2n+4 | | -9.5-3.5x=-7.5x-1.5 | | t*7-26=128 | | 6+.02x=0.8x-3 | | −2x−14=−2 | | (2x−1)(x+5)=0 | | -12x-18=-144 | | 1–2y=10 | | (1–2y)2= | | 7x-40=2x+75 | | 2y+22=5y+10 | | 2(2x-1)-3(x+5)=5x-(3x-3) | | -0y+6=-18+3y | | 4h+19=-2-17 | | -42a-3=1/210-2a | | 1.5x+1=1.6 | | 3x-8=-x+9-5 | | 2k+9=2k-12 | | 5/2v=3 | | 8k=56.k= | | (D2+3)(d2+2d+1)=0 | | 3x²-7x-x=0 | | 12+6y=2y+36 | | 2p+p=20+5 | | 5y+2=8y-7 | | 5y+2=8y+7 | | 6x+5=−6x+5 | | (5+5x)/(5+2x)-1=0 | | -4x+(5/8)=(3/4 |